Evaluation Of The Reading Speed Of Near Visual Acuity After Providing Low Vision Intervention (Indian Journal of Applied-Basic Medical Sciences, 2021)
BACKGROUND: The prevalence of low vision has been increased overtime. So many different types of low  vision devices were developed within few years. From so many studies, it has been proved that  low vision rehabilitation is the better option for low vision patients to improve their quality of  life. Low vision rehabilitation will improve quality of life of patients by enhancing their  residual vision for distance as well as for near activities. Reading speed for near activities is  also an important part for development of reading ability, their confidence and their  performance. So, in this study, reading speed will be measured with the help of MN Read chart  (continuous text chart) and thereby evaluate improvement in reading speed after providing low  vision devices for near. METHOD: This study is cross sectional in which 102 Patients were enrolled in the study visited at Shri C.  H. Nagri Municipal Eye hospital (Tertiary eye care center). All patients were undergoing a  standardized ophthalmological examination. Best corrected visual acuity for distance and near  has been assessed. Starting point of magnification required for low vision patients has been  calculated and was finalized according to their visual ability, needs and demands, occupation  and affordability. Then, according to needs of Low Vision Patients, Low Vision Intervention  has been given with proper training and finally Reading Speed being measured with final  recommended Low Vision Aid. After provision of low vision aids, reading speed is evaluated  using standardized MN Read text chart. Reading speed has been measured according to Word  per Minute formula. RESULTS:  102 low vision patients were enrolled in the study, who visited tertiary eye care center, among  which 53.92% were male population and 46.08% were female population. Mean Reading speed  was 43.82±24.73 wpm after provision of low vision aids for the whole group. Three major  causes were found more common; Chorio-Retinal Coloboma (22.54%), Retinal detachment  (15.68%) and Retinitis Pigmentosa (13.72%). The management of all low Vision patients was  found to be different for distance and near according to the patients Visual Acuity, needs and  affordability.  CONCLUSION:This indicates the great value of low vision rehabilitation through adequate providing of low  vision aids for the improvement of reading ability. Low vision Intervention will help patient to  maintain and regain their reading ability, which can lead to an increase in independency, mental  ability, confidence and quality of life.
Keywords: near visual acuity; low vision intervention; intervention